Development and validation of an automatic all‐wheel steering system for multiple‐articulated rubber‐tire transit. Issue 3 (9th April 2021) - Feng, Jianghua; Hu, Yunqing; Yuan, Xiwen; Huang, Ruipeng; Zhang, Xinrui; Xiao, Lei
Abstract: When driving a 32‐m long multi‐set rubber‐tire transit in a manual driving mode, it is easy for the driver to feel tired due to the massive concentration, and it is hard to manually operate in a narrow and twist gauge. The authors introduce a six‐axle coordinated automatic all‐wheel steering control system and its design method is based on the visual perception and the geometric relationship. First, the functions of the two subsystems of the full‐axle automatic steering control system are introduced. One subsystem is a path tracking control system and the other subsystem is a trajectory following the control system. Secondly, the theoretical principles of the two control systems are introduced in detail. Then, the controller design method of the two subsystems is introduced. Finally, the simulation results of Trucksim and MATLAB/Simulink are compared with the actual vehicle test data to test the controller's perception and the follow‐up control effect. It can be concluded that the gap between the platform and the train is kept between a relatively 10∼20 cm narrow when the train pulls in and out of the station. When the train runs at a high speed, it is stabilised at 72 km/h, and the lateral deviation from the virtual track centreline is controlled within ±15 cm.